Partnership on the high seas: China and Russia's joint naval manoeuvres - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2019)
On the occasion of the 70th founding anniversary of China's national navy, a big naval parade with more than 30 Chinese ships sailed off the coast of Qingdao. A few days later, on 29 April 2019, the 'Joint Sea 2019' Russian-Chinese bilateral naval exercise began. In numbers, China's navy now has the world's biggest fleet - also thanks to decades of Russian naval armament. From Beijing's point of view, however, the Chinese armed forces have a serious shortcoming: a lack of operational experience. Here, too, Moscow fills some gaps. Since the first joint manoeuvre in 2005, cooperation has increased at many levels. Sino-Russian sea manoeuvres now also serve as a menacing signal of support for China's claims in the South China Sea or in the Sino-Japanese disputes in the East China Sea. Moscow and Beijing use the joint naval exercises to set geopolitical signals. Despite all historic mistrust, Sino-Russian cooperation seems to rest on a relatively stable foundation of partnership. But maritime cooperation and coordinated partnership must not lead to an alliance.
Keywords: 320